Genetic determination of islet cell autoimmunity in monozygotic twin, dizygotic twin, and non-twin siblings of patients with type 1 diabetes: prospective twin study. Issue 7185 (13th March 1999) - Redondo, Maria J; Rewers, Marian; Yu, Liping; Garg, Satish; Pilcher, Colleen C; Elliott, Robert B; Eisenbarth, George S
Abstract: Objective: To test the hypothesis that non-diabetic dizygotic and monozygotic twin siblings of patients with type 1 diabeteshave a similar high prevalence of islet cell autoantibodies, thus suggesting that islet cell autoimmunity is mainly environmentally determined. Design: Prospective twin study. Setting: Two specialist centres for diabetes in the United States. Participants: Non-diabetic monozygotic twin (n=53), dizygotic twin (n=30), and non-twin (n=149) siblings of patients with type 1 diabetes; 101 controls. Main outcome measures: Analysis of progression to diabetes and expression of anti-islet autoantibodies. Results: Monozygotic twin siblings had a higher risk of progression to diabetes (12/53) than dizygotic twin siblings (0/30; P<0.005). At the last follow up 22 (41.5%) monozygotic twin siblings expressed autoantibodies compared with 6 (20%) dizygotic twin siblings (P<0.05), 16 (10.7%) non-twin siblings (P<0.0001), and 6 (5.9%) controls (P<0.0001). Monozygotic twin siblings expressed multiple (≤2) antibodies more often than dizygotic twin siblings (10/38 v 1/23; P<0.05). By life table analysis the probability of developing positive autoantibodies was higher among the monozygotic twin siblings bearing the diabetes associated HLA DQ8/DQ2 genotype than in those without this genotype (64.2% (95% confidence interval 32.5% to 96%) v 23.5% (7% to 40%) at 10 years of discordance; P<0.05). Conclusion: Monozygotic and dizygotic twins differ in progression to diabetes and expression of islet cell autoantibodies. Dizygotic twin siblings are similar to non-twin siblings. These two observations suggest that genetic factors play an important part in determination of islet cell autoimmunity, thus rejecting the hypothesis. In addition, there is a high penetrance of islet cell autoimmunity in DQ8/DQ2 monozygotic twin siblings.